SINERGITAS PEMERINTAH DESA BERSAMA MASYARAKAT TERHADAP PENCEGAHAN NARKOBA - Syahraini, Silva; Mustanir, Ahmad; Razak, Muhammad Rais Rahmat (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2024)
The purpose of the research is to find out how the Synergy of the Village Government with the Community Towards Drug Prevention (Case Study in Teteaji Village) and the supporting and inhibiting factors in implementing the Synergy of the Village Government with the Community on Drug Prevention (Case Study in Teteaji Village). The data collection techniques used in this study are documentation, interviews, and literature studies. The data collected is then processed and analyzed using software analysis techniques such as Nvivo 12 plus. The use of this software allows the data that has been collected to be more structured, organized, and meaningful. Research Results This research focuses on the synergy between the village government and the community in drug prevention efforts in Teteaji Village. A qualitative approach is used to deeply understand how interaction and cooperation between the village government and the community can prevent drug abuse. The results of the study show that synergy built through effective communication, appropriate feedback, and trust, is very important in creating an environment that supports drug prevention. However, there are several obstacles, such as diverse levels of education and lack of information facilities, that hinder the effectiveness of this program. Therefore, a more personal and participatory approach is needed to increase public understanding and involvement in drug prevention programs. This research is expected to contribute to the development of more effective drug prevention strategies at the village level.